Exclusive neoadjuvant chemotherapy in locally advanced resectable gastric and gastro-esophageal junction adenocarcinoma. Issue 5 (May 2017) - Fernandez, Eugenio; Cacheux, Wulfran; Frossard, Jean-Louis; Koessler, Thibaud; Abou, Magali; Moniez, Michael; Huber, Olivier; Puppa, Giacomo; Roth, Arnaud
Abstract: Background: Perioperative chemotherapy improves the prognosis of patients with locoregionally advanced resectable gastric and gastro-esophageal junction adenocarcinoma. Nevertheless, only 50% of operated patients could receive the postoperative component chemotherapy. An exclusive preoperative chemotherapy is therefore an interesting strategy. We report the clinical course of patients with operable gastric and gastroesophageal junction adenocarcinoma treated with an intention of exclusive preoperative chemotherapy. Methods: The medical records of all consecutive patients with an operable gastric or gastroesophageal junction adenocarcinoma and treated with an intention of exclusive preoperative chemotherapy were analysed. Results: Between 1999 and 2014, 90 eligible patients were identified. Fifty-eight patients (64%) presented with clinical T3–T4 tumour and 63 (70%) had a lymph node involvement. Eighty (90%) patients were treated with 4 cycles of preoperative chemotherapy containing docetaxel, 5-fluorouracil (5FU) and a platinum salt. All patients had surgery with a D2 lymphatic dissection and R0 resection rates in 91% and 88% respectively. Median progression-free survival was 6.1 years (95% confidence intervals (CI): 1.6, NC) with median overall survival of 8.1 years (95% CI: 4.1, NC). Conclusion: Our study suggests that an exclusive neoadjuvant approach when associated with a D2 lymph node dissection in resectable gastric and gastro-esophageal junction adenocarcinoma appears a feasible strategy with encouraging survival.